Helmintos de la República de Costa Rica XX. Algunos tremátodos de aves silvestres - Brenes, Rodrigo Ramón; Arroyo, Guido (Revista de Biología Tropical, 1962)
Several new species of trematodes are described: Leucochloridium costarícense (Brachylemidae), from the small intestine of Gymnostinops montezuma; Eumegacetes macfoorcbis (Lecithodendriidae), from the cloaca of Crotophaga sulcirostris; Cyclocoelum (Hyptiasmus) costaricense (Cyclocoelidae) from the air sacs and thoracic cavity of Momotus momota conexus; Cyclocoelum (Hematotrephts) facioi, from the air sacs of jacana spinosa spinosa; Tanaisia winteri(Eucotylidae), from the kidney of J. s. spinosa, and T. freitasi, from the kidney of G. montezuma. Platynosomum illiciens (Dicrocoeliidae) is redescribed from specimens found in the gall bladder of Leucopternis semiplumbea.